2018
DOI: 10.1038/s41598-017-18957-9
|View full text |Cite
|
Sign up to set email alerts
|

Multi-wavelength growth of nanosecond laser-induced surface damage on fused silica gratings

Abstract: The nanosecond laser-induced damage growth phenomenon on the exit surface of fused silica grating is investigated at 1064 nm and 355 nm separately and also simultaneously. Experiments are first carried out on damage sites on a plane fused silica sample showing two different morphologies, and a damage type is selected for ensuring the repeatability of the subsequent tests. Comparing the mono-wavelength growth results on a grating and a plane fused silica sample, the periodic surface structure is found to be an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…One of the significant findings is that growth temperature is an important factor determining the degree of phenotypic variation. Though phenotypic variation helps bacteria to develop resistance for surviving under harsh environments 52 , this variation makes the bacteria less desirable as a BCA. This problem can be overcome by altering the growth temperature during mass production.…”
Section: Discussionmentioning
confidence: 99%
“…One of the significant findings is that growth temperature is an important factor determining the degree of phenotypic variation. Though phenotypic variation helps bacteria to develop resistance for surviving under harsh environments 52 , this variation makes the bacteria less desirable as a BCA. This problem can be overcome by altering the growth temperature during mass production.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, the Maxwell equations are used as governing equation to solve the electromagnetic wave propagation characteristics during the laser action 15,26 . Due to the fact that the surface defect of KDP crystal in practical engineering is far smaller than the spot size of internal optical path in large laser system, we assume that the incident light is a harmonic plane electromagnetic wave and the equations can be simplified to the Helmholtz equation, as Eq.…”
Section: Model and Theorymentioning
confidence: 99%
“…The main mechanisms of laser-induced damage of femtosecond pulse lasers and nanosecond pulse lasers are intrinsic ionization and defect-based heat absorption, respectively [14][15][16][17] . Because the duration of nanosecond laser damage is longer, multiple physical mechanisms like light modulation, heat absorption, fluid flow, etc.…”
mentioning
confidence: 99%
“…Nevertheless, it is found that surface structures such as pits, scratches, cracks, etc., are prone to induce laser damage in KDP crystals. 15 17 Because of the poor physical properties of KDP materials, like soft and brittle characteristics, temperature sensitivity, high water deliquescence, etc., it is inevitable to generate defects on the surface of the crystal during single-point diamond turning (SPDT) processes. 18 , 19 Nowadays, in the course of the development of KDP crystals with excellent quality and power-handling capability, the problem of laser-induced damage has shifted from the bulk to the surface.…”
Section: Introductionmentioning
confidence: 99%